2011
DOI: 10.1038/hdy.2011.62
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis, phenotypic disequilibrium and contrasting associations with climate in the land snail Theba pisana

Abstract: Hotter conditions favour effectively unbanded (EUB) shells in the snail Theba pisana. T. pisana is also polymorphic for colour of the shell's apex, determined by a pair of alleles at a locus linked to the banding locus. Apex colour is epistatic to shell banding, such that banded snails with a dark apex have darker bands. Annual censuses over 22 years across an ecotone between a sheltered Acacia thicket and open dune vegetation showed a persistent association of both EUB shells and pale apex with the Open habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The banding of shells has a well‐characterized genetic background (Cowie, ; Jones et al, ; Murray, ) but suppression of pigmented bands in Cepaea nemoralis by expression of the hyalozonate gene is a long‐known phenomenon by which the phenotype of the shell can be modified (Cain, Sheppard, & King, ). In contrast to a directed selection (Johnson, , ), Köhler et al () who used a dataset of Cowie () showed high winter and spring temperatures to be associated with high variation in morph frequencies but not with the frequency of a particular morph. Also, a study on the phenotypic disequilibrium in a large dataset obtained for Cepaea nemoralis suggested that selection has favored combinations of common morphs, whichever they were (Cook, ).…”
Section: Morphological Adaptationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The banding of shells has a well‐characterized genetic background (Cowie, ; Jones et al, ; Murray, ) but suppression of pigmented bands in Cepaea nemoralis by expression of the hyalozonate gene is a long‐known phenomenon by which the phenotype of the shell can be modified (Cain, Sheppard, & King, ). In contrast to a directed selection (Johnson, , ), Köhler et al () who used a dataset of Cowie () showed high winter and spring temperatures to be associated with high variation in morph frequencies but not with the frequency of a particular morph. Also, a study on the phenotypic disequilibrium in a large dataset obtained for Cepaea nemoralis suggested that selection has favored combinations of common morphs, whichever they were (Cook, ).…”
Section: Morphological Adaptationsmentioning
confidence: 98%
“…This mechanism, however, cannot explain the maintenance of variation in uniformly hot habitats. Although to date there are not many studies statistically linking morph frequencies of snails to environmental parameters such as heat, three of them (Johnson, , ; Köhler et al, ) have identified moderately elevated temperatures acting on free‐living populations of Theba pisana in the middle of their lifetime as a key element for the variation in shell coloration. The studies of Johnson (, ) found hot summer conditions to increase the frequency of unbanded morphs in T heba pisana , attributing this phenomenon to climate selection.…”
Section: Morphological Adaptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be particularly true for populations subjected to strong bottle-necks caused by, for example, high ambient temperatures. In T. pisana, high temperatures emerged either as a selective force or an epigenetically acting component of the environment (Johnson 2011(Johnson , 2012Köhler et al 2013): organisms possess various mechanisms to deal with high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast to other helicid snails such as Cepaea , which display distinct coloration and banding patterns, the polymorphism of T. pisana is multiform, with lots of variation within morphs, especially of the intensity of coloration of the bands. The interplay of genetic variation and presumed phenotypic plasticity leads to almost every individual expressing an apparently unique banding pattern as documented by Cowie () and Cain (), and as recently quantified by Johnson () for the intensity of banding. Even though Cowie (, ) scored all morphs on the ‘juvenile’ part of their shells, he pointed out that ‘virtually all shells’, also those scored as ‘unbanded’, ‘acquire some banding on later whirls.…”
Section: Discussionmentioning
confidence: 99%